2006
DOI: 10.1093/bjsw/bch405
|View full text |Cite
|
Sign up to set email alerts
|

Genealogy's Desire: Practices of Kinship Amongst Lesbian and Gay Foster-Carers and Adopters

Abstract: Background: Cognitive Muscular TherapyTM (CMT) is an integrated behavioural intervention developed for knee osteoarthritis. CMT teaches patients to reconceptualise the condition, integrates muscle biofeedback and aims to reduce muscle overactivity, both in response to pain and during daily activities. This nested qualitative study explored patient and physiotherapist perspectives and experiences of CMT.Methods: Five physiotherapists were trained to follow a well-defined protocol and then delivered CMT to at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 28 publications
0
56
0
Order By: Relevance
“…Perhaps the most substantial research conducted in the UK around gay and lesbian adoption and fostering, is that carried out by Hicks (1996Hicks ( , 1998Hicks ( , 2000Hicks ( , 2006aHicks ( b, 2008aHicks ( b, 2011Hicks ( , 2013, and Hicks and McDermott (1999). Building on the initial findings of Skeates and Jabri (1988), their work identified that gay and lesbian applicants were often associated with a degree of 'risk' and were closely scrutinised during assessment.…”
Section: Research With Gay and Lesbian Adopters And Foster Carersmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the most substantial research conducted in the UK around gay and lesbian adoption and fostering, is that carried out by Hicks (1996Hicks ( , 1998Hicks ( , 2000Hicks ( , 2006aHicks ( b, 2008aHicks ( b, 2011Hicks ( , 2013, and Hicks and McDermott (1999). Building on the initial findings of Skeates and Jabri (1988), their work identified that gay and lesbian applicants were often associated with a degree of 'risk' and were closely scrutinised during assessment.…”
Section: Research With Gay and Lesbian Adopters And Foster Carersmentioning
confidence: 99%
“…Gender role modelling still needs reconsidering, so that professionals undertake a more nuanced approach to gender (Hicks, 2008b). Similarly, whilst the cultural reverence for the nuclear family and relationships based solely on biological relatedness has been challenged elsewhere (Hicks, 2006a(Hicks, , 2014, this is still implicit in many key stages of the process. Adoption in particular, remains embodied within an assumption of applicant infertility, although lesbian and gay candidates do not necessarily experience this in the same way.…”
Section: Implications For Practicementioning
confidence: 99%
“…Both Australian and international research on lesbian and gay foster carers has to date produced an overwhelmingly negative image of child protection systems. This research highlights at least five areas where discrimination occurs against lesbian and gay foster carers: (1) 'considerable scrutiny of their parenting ability and capacity to raise children' (Brooks and Goldberg 2001, 154;Riggs 2006b); (2) 'outright rejection… on the basis of their sexuality alone' (Hicks 2005b, 43-44); (3) an implicit expectation to 'educate social workers' about issues pertaining to non-heterosexual people in order to be fairly considered as applicants (Hicks 2005b;Riggs 2007); (4) the prevalence of a 'don't ask don't tell' policy that has until recently been implicit to UK assessment procedures (Hicks 2000) and which US research suggests continues to be implicit to US assessment procedures (Matthew and Cramer 2006); and (5) requests made to lesbian and gay applicants to demonstrate that they will provide appropriate 'opposite sex role models' to children in their care (Hicks 2000;Riggs and Augoustinos 2009). …”
Section: Previous Research and The Australian Foster Care Contextmentioning
confidence: 99%
“…In the context of child protection, research suggests that this can be potentially beneficial for children in care. A key example of this is the suggestion that many lesbians and gay men consider fostering as a first option for starting a family, rather than as 'second best' to biological reproduction (Hicks 2005b;Mallon 2006). Mallon infers from this that lesbian and gay carers often succeed in caring for children with high needs as a result of this commitment to foster parenting as a first option.…”
Section: Previous Research and The Australian Foster Care Contextmentioning
confidence: 99%
“…The longitudinal design of the NLLFS is considered one of the most effective methods of documenting the psychosocial evolution of contemporary families (Hicks, 2005;Lambert, 2005). The aim of this study on planned lesbian families is to report on the innovative parenting styles of lesbian mothers, to assess the effects of homophobic stigmatization on the psychological development of the children, and to explore ways of reducing the impact of homophobia on children's lives and well-being (Gartrell et al, 1996).…”
Section: Historical Cultural Milieumentioning
confidence: 99%